The Impact of Healthy Leader and Organization Climate on Teacher Well-being: Self-Efficacy as an Intervening and Meaningful Work as a Moderating - Wahyudi Triwiyanto; Fathur Rokhman; Joko Sutarto; Tri Suminar (International Conference on Science, Education, and Technology, 2023)
This study examines the effect of "healthy leader", "organizational climate" on "teacher well-being" which is mediated by "self-efficacy" and moderated by "meaningful work." The data were obtained from a sample of 92 teachers using a questionnaire. Data were analyzed using SEM (Structural Equation Modeling) analysis techniques and SmartPLS as software to perform model analysis as well as test hypotheses. The interpretation of the results of the smartPLS analysis uses 2 stages, namely the outer model testing stage and the inner model testing stage. The results of this study indicate that organization climate has a positive and significant influence on teacher well-being. Meaningful work strengthens the influence between healthy leaders and teacher well-being, and the influence of organizational climate on teacher well-being. Meaningful work weakens the effect of self-efficacy on teacher well-being.